The Effect of Financial Technology and Financial Inclusion on UMKM Performance with Financial Literacy as an Intervention Variable (Case Study of MSMEs Using Bank Mandiri's Livin Merchant in Bandung City) - Anggraeni, Dwi Retno; Rendy, Pras; Mulyana, Asep; Sutisna, Sutisna (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Data from the Ministry of Cooperatives and SMEs, the number of MSMEs in Indonesia reached 64.2 million and contributed 61.07 percent or 8,573.89 trillion rupiah to GDP. The largest MSMEs throughout Indonesia are dominated by Java Island, the first position as the province with the most MSMEs, namely West Java with 1,494,723 units.MSMEs experience delays in their development and find it difficult to move up a class because MSMEs do not have an innovation concept, an unstructured financial management system and a business pattern that follows current developments due to a lack of financial literacy.Bank Mandiri as a State-Owned Enterprise which is a leading Wholesale Bank in financing, including as a Bank that has the best digital banking product innovation that encourages the growth of MSMEs. Bandung City is one of the cities with the most MSMEs and utilizes services from Bank Mandiri in the form of Livin Merchant, which helps in managing MSME finances and facilitates MSME access to obtain capital loans from the Bank. The research conducted used the Balanced Scorecard as a measure of business performance. Based on the results of a Pre-survey of 30 MSME actors registered as Livin Merchant users in Bandung City randomly, it was obtained that MSME actors had a lack of knowledge in the financial perspective. The variables measured in the study used Financial Technology, financial inclusion and financial literacy as intervening variables on MSME performance.